Evaluation of 32 mm Automatic Hair Curlers on Shopee Using AHP Customer Reviews - Alya Esa Mentari; Ari Muzakir (Universitas Mercu Buana Yogyakarta, 2026)
Abstract This study aimed to evaluate 32 mm automatic hair curler products available on the Shopee e-commerce platform by applying the Analytic Hierarchy Process (AHP) combined with customer review analysis. The data were obtained through direct observation of three products with similar characteristics. The collected data included product ratings, number of reviews, star-based review distribution, sales volume, and price. Sentiment analysis was conducted by categorizing customer reviews into positive, neutral, and negative groups based on their star distribution. The AHP method was used to determine the priority weights of each evaluation criterion. The results showed that sales volume was the most influential criterion in the decision-making process, followed by product ratings and the number of reviews. The final AHP score revealed that the MAIMEITE product achieved the highest value, making it the most recommended option. This study demonstrated that integrating AHP with customer review analysis provided an objective, systematic, and data-driven approach to product evaluation.